Local Wisdom Becomes the Commander in Criminal Resolution - Andriyani, Andriyani; Dewi, Rusmala (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Settlement of criminal cases through peaceful means is highly recommended, especially in minor criminal cases. This is important so that cases do not accumulate. This method is widely applied in customary law which prioritizes restorative justice. However, not all customs that exist in society can be accepted by Islamic law. Therefore, this research conducted a study of the